THE IMPACT OF FAMILY VIOLENCE ON THE SOCIAL AND PSYCHOLOGICAL DEVELOPMENT OF THE CHILD - AL MAJALI, S.; ALSREHAN, H (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT Children may become victims of physical, sexual, emotional abuse. Our research aims to evaluate the effect of family violence on the child's social and psychological adaptation. 456 UAE University students voluntarily participated in the study. Child Abuse and Trauma Scale (CATS) were used to determine the level of domestic violence. A methodology-questionnaire of Rogers-Diamond was used to determine the degree of social and psychological adaptation. As a result of the study, it was determined that students with a high level of domestic violence have a low level of social and psychological adaptation of less than 20%.RESUMEN Los niños pueden convertirse en víctimas de abuso físico, sexual y emocional. Nuestra investigación tiene como objetivo evaluar el efecto de la violencia familiar en la adaptación social y psicológica del niño. 456 estudiantes de la Universidad de EAU participaron voluntariamente en el estudio. La Escala de Abuso Infantil y Trauma (CATS) se utilizó para determinar el nivel de violencia doméstica. Se utilizó un cuestionario metodológico de Rogers-Diamond para determinar el grado de adaptación social y psicológica. Como resultado del estudio, se determinó que los estudiantes con un alto nivel de violencia doméstica tienen un bajo nivel de adaptación social y psicológica de menos del 20%.